EFEITOS DA LUZ DE UM FOTOPOLIMERIZADOR LED NA TEMPERATURA PULPAR BASAL IN VIVO EM PRÉ-MOLARES HUMANOS E SUA CORRELAÇÃO COM AS CARACTERÍSTICAS ANATÔMICAS DENTAIS EX VIVO - Runnacles, Patricio (2014)
Objective: This in vivo study evaluated the baseline pulp temperature in human intact upper premolars and the pulp temperature rise induced by light emitted by a high power polywave Light Emitting Diode (LED) light curing unit (LCU); also, the possible correlation between the change in temperature (ΔT) and the volume of the crown and the pulp chamber ex vivo. Material and methods: after approval of the local Ethics Committee was obtained (protocol #255,945), upper right and left first premolars requiring extraction for orthodontic reasons from 8 volunteers (n=15) received infiltrative and intraligamental anesthesia and were isolated using rubber dam. A small, occlusal preparation was made using high-speed hand piece, under constant air-water spray, until a minute pulp exposure was attained. The sterile probe from a wireless, NIST-traceable, temperature acquisition system (Temperature Data Acquisition - Thermes WFI, Physitemp) was inserted directly into the coronal pulp. Once the baseline pulp temperature was stable, the buccal surface was exposed to polywave light from a LED LCU (Bluephase 20i, Ivoclar Vivadent) using selected EMs: 10-s either in low (10-s/L) or High (10-s/H); 5-s-Turbo (5-s/T); and 60-s-High (60-s/H) intensities, allowing a 7-min span between each exposure. Peak PT values and PT increases from baseline (ΔT) after exposure were subjected to 1-Way, repeated measures ANOVAs, and Bonferroni's post-hoc tests (α=0.05). Linear regression analysis was performed to establish the relationship between applied radiant exposure and ΔT. Linear regression analysis was performed to establish the relationship between applied radiant exposure and ΔT. the teeth were extracted according to treatment plan. The crown and pulp volumes were measured using micro-tomography scanner, and pulp chamber / crown volume ratio was determined. Afterwards, premolar buccal-lingual, cervico-occlusal, mesio-distal dimensions as well as between cusp distances were measured using a digital caliper. Results: consistent temperature below body temperature, resulting in an average core temperature of 35 ° C (+ 0.7 ° C) was found. All modes of activation of the LED promoted significant temperature rise in the pulp chamber. A positive correlation between energy density and thermal variation was observed. No correlation was observed between coronal volume, the pulp chamber with temperature changes. A significant negative correlation was noted between pulp temperature changes when 10-s/L was used and VL.